Reliability of an Audit Tool to Measure Healthy Food Availability in Food Outlets across Baltimore City. Issue 5 (2nd September 2020) - Misiaszek, Caitlin; Kvit, Anton; Burns, Carrie; Harding, Jamie; Buczynski, Amanda; Freishtat, Holly; Bassarab, Karen; Bilal, Usama; Palmer, Anne
ABSTRACT: The objective of this study was to measure the reliability of an index to assess healthy food in food stores. Food stores across Baltimore City were assessed using the Healthy Food Availability Index-Brief (HFAI-B) tool and resulting HFAI-B score. Reliability was measured using the Pearson correlation for the HFAI-B score, and Cohen's Kappa for other binary and categorical store parameters. All items included in the HFAI-B score had high inter-rater and test-retest reliability. The Pearson Correlation coefficient for HFAI-B scores between and within observers was very high. The HFAI-B is a reliable measure to assess the availability of healthy foods in food stores.